Dendritic lamellar assembly in solution-cast poly(l-lactic acid) spherulites. Issue 40 (28th September 2017) - Chen, Hsin-Ping; Woo, Eamor M.
Abstract : PLLA crystallized by solvent evaporation in THF in open atmosphere exhibits a one-ring or two-ring birefringence-banded morphology with dendritic lamellae arranged in multi-layers and shaped as a dome. Abstract : Poly(l -lactic acid) (PLLA) interacts with solvents of different interaction strengths and crystallizes, upon solvent evaporation, into spherulites with various birefringence patterns. The top surface-relief morphologies associated with interior lamellae assembly in solvent-evaporated PLLA confined films are probed using atomic force, scanning electron, and polarized-light microscopy techniques. For PLLA crystallized upon solvent evaporation, the type of solvent, solvent evaporation rate and evaporation temperature lead to a wide variety of morphologies with complex optical birefringence patterns. PLLA crystallized by solvent evaporation in open atmosphere with tetrahydrofuran (THF) as the solvent exhibits a one-ring or two-ring birefringence-banded morphology at 26–30 °C, and its lattice belongs to α-crystals without occurrence of complexation with any solvent molecules. When PLLA is cast from solvents other than THF or temperatures outside the range of 26–30 °C, no banded spherulites are formed. The topography of the banded PLLA spherulites demonstrates that the dendritic petal-like lamellae are arranged in multi-layered tree-branch patterns. In addition, inside the spherulites, the lamellae are arranged in a radial direction, and a layered structure is seen from the lateral view.